Wear of polyethylene and polyurethane elastomers used for components working in natural abrasive environments. (August 2021) - Ligier, Krzysztof; Olejniczak, Klaudia; Napiórkowski, Jerzy
Abstract: This paper presents the results of research on an evaluation of the intensity of tribological wear of polymers used for machinery components. The research material consisted of four types of polyurethane and PE 1000 PE-UHMW polyethylene. The research on the intensity of abrasive wear employed two methods: ball-cratering and the spinning bowl method. The ball-cratering test was performed using an abrasive suspension made of distilled water and silicon carbide (SiC). For the "spinning bowl" method, clay was the abrasive material. Based on material mass and density loss measurements, volumetric wear of the samples, and the specific wear rate Kc was determined. According to the test results, polyethylene PE 1000 was characterized by the highest resistance to wear. In the spinning bowl test, a similar wear value was obtained for polyurethane elastomer of the highest hardness among the tested polyurethanes. Highlights: The mechanical properties of polymers influence their resistance to abrasion in natural abrasive The type of natural soil affects the intensity of wear The wear resistance test should be performed in conditions closest to the operating conditions